Dynamin function is important for chemokine receptor‐induced cell migration. (9th September 2015) - Jacques, Richard O.; Mills, Shirley C.; Cazzonatto Zerwes, Paula; Fagade, Feyisope O.; Green, John E.; Downham, Scott; Sexton, Darren W.; Mueller, Anja
<x xml:space="preserve">Abstract</x> The HIV viral entry co‐receptors CCR5 and CXCR4 function physiologically as typical chemokine receptors. Activation leads to cytosolic signal transduction that results in a variety of cellular responses such as cytoskeletal rearrangement and chemotaxis (CTX). Our aim was to investigate the signalling pathways involved in CC and CXC receptor‐mediated cell migration. Inhibition of dynamin I and II GTPase with dynasore completely inhibited CCL3‐stimulated CTX in THP‐1 cells, whereas the dynasore analogue Dyngo‐4a, which is a more potent inhibitor, showed reduced ability to inhibit CC chemokine‐induced CTX. In contrast, dynasore was not able to block cell migration via CXCR4. The same activation/inhibition pattern was verified in activated T lymphocytes for different CC and CXC chemokines. Cell migration induced by CC and CXC receptors does not rely on active internalization processes driven by dynamin because the blockade of internalization does not affect migration, but it might rely on dynamin interaction with the cytoskeleton. We identify here a functional difference in how CC and CXC receptor migration is controlled, suggesting that specific signalling networks are being employed for different receptor classes and potentially specific therapeutic targets to prevent receptor migration can be identified. Copyright © 2015 John Wiley & Sons, Ltd.